Characteristic of human arm frequency radiation - A. Jalil, Siti Zura (2012)
Many studies have indicated that there are endogenous electromagnetic fields generated by the human body. All the living body, especially the human being is believed to have their own radiation which the field radiates into space around on the body. With the advancement of science and technology, this radiation field can be described as the vibration of electromagnetic (EM) field generated by the human body. The field penetrates the physical body and emits their characteristics radiations of frequency. This work discusses the analysis of frequency radiation on human arm and classifies the characteristic of human arm radiation based on gender. The human radiation frequency is experimentally studied from 33 healthy human subjects of 17 males and 16 females. The frequency radiation is obtained from 6 points of human arm on left-side and right-side of human body. The statistical technique is used to examine the characteristic of radiation frequency. The multivariate analysis of variance (MANOVA) is employed to compare the characteristic of radiation frequency differences between genders. Prior to MANOVA analysis, several preliminary assumptions testing were performed, which it is confirmed that no serious violations noted in the tests and met the MANOVA assumptions. The results of MANOVA indicate there is statistically significant difference among gender of males and females on a linear combination of human arm frequencies radiation. It is confirmed that the population means on a set of human arm frequencies varies across gender. Then, k-nearest neighbor (k-NN) technique is employed for classification. The default neighborhood setting of Euclidean Distance is used to find nearest neighbors. The results show that the k-NN produced 89% of correctly classified, which suggested that the k-NN classifier is able to classify human arm radiation frequency.